Spectra of the geomagnetic field diurnal variations - I. I. Rokityansky; A. V. Tereshyn (Geofizičeskij žurnal, 2019)
Spectral analysis of the geomagnetic field time series with the discreteness of 60 s (Intermagnet data) and a duration of, for example, 1 year (31×106 s) yields an average-annual amplitude spectrum over periods from approximately 500 s to 5×106 s. The spectrum consists of the continuous part (continuum spectrum) and narrow lines at the diurnal period T0=86400 s and its harmonics with periods T=T0/n, where n=2—7. The subject of this work is the diurnal line of the spectrum and its harmonics. The average-annual spectra of the geomagnetic field diurnal variations of 32 Intermagnet observatories in North America were calculated. Also the average-seasonal spectra of five observatories, which represent high, medium and low geomagnetic latitudes of both northern and southern hemispheres were obtained. At the near-pole high geomagnetic latitudes, only the daily harmonic T0 is observed, at the geomagnetic equator 7 harmonics are observed, in the aurora zone and middle latitudes — an intermediate number of harmonics: from two to seven. The amplitude is maximal at high latitudes (50—80 nТ), less at the geomagnetic equator (≈40 nТ), and quite minor at middle latitudes (10—15 nТ). These results are in good agreement with the known data on diurnal variations. The used representation of the harmonics of diurnal period by spectral lines makes it easy and clearly to track the features of diurnal variations and their changes both according to the data of individual observatories and synchronous data of many observatories. An interesting new scientific result is the detected widening of the diurnal harmonic spectral line from September to February and the absence of the widening from March to August for all three considered years 2009—2011 at all five observatories. This is not a seasonal variation, since it is equally observed at observatories in both the northern and southern hemispheres, in which the seasons are in antiphase. We can assume that this phenomenon is associated with a certain orientation of the Earth in outer space relative to some factor that changes the daily spectral line to a wider one. The absolute motion of the Earth, formed by a hierarchy of cosmological rotations, is supposed as such a factor. A brief review of the literature on the determination of the parameters of absolute motion is given.